Lingering Shadows: A Short Story Collection Highlighting The Effects of Survivor’s Guilt in Indonesian Society - Kelly Aurelia; Ribut Basuki (Institute of Research and Community Outreach - Petra Christian University, 2025)
Survivor’s guilt is a psychological phenomenon that may occur when an individual survives a traumatic event while others are left injured or lose their lives. Although the concept has been around since the 20th century, it remains not widely acknowledged despite its serious consequences. Recognizing this underrepresentation, this thesis examines the long-term effects of survivor’s guilt as researched by Bistas and Grewal, and O'Connor, Berry, and Weiss. These effects are categorized into two main types: mental effects, which include obsessive thinking, post-traumatic stress disorder (PTSD), and depression; and social effects, such as interpersonal sensitivity, hostility, and social isolation. These issues are explored through a creative work in the form of a short story collection, featuring four characters from diverse backgrounds and ages. While the survivors’ experiences are also shaped by environmental responses, the effects significantly impact their mental state and their ability to form relationships in social settings.